(untitled) (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
Idioms, as linguistic expressions embedded in cultural contexts, offer profound insights into the collective values, beliefs, and philosophies of societies. This article explores the cultural and philosophical dimensions of studying idioms related to life, such as those expressing existence, mortality, and human experience. By analyzing idioms across diverse linguistic and cultural frameworks, this study highlights their role in shaping worldviews and transmitting philosophical ideas. Employing a comparative linguistic approach, the research reveals how idioms reflect universal human concerns while preserving cultural distinctiveness. The findings underscore the significance of idioms as a bridge between language, culture, and philosophy, offering valuable perspectives for cross-cultural understanding and humanistic inquiry.